From the Laboratory to the Classroom: The Potential of Functional Near-Infrared Spectroscopy in Educational Neuroscience - Brockington, Guilherme; Balardin, Joana Bisol; Zimeo Morais, Guilherme Augusto; Malheiros, Amanda; Lent, Roberto; Moura, Luciana Monteiro; Sato, Joao R. (Frontiers in Psychology, 2018)
Paralleling two decades of growth in the emergent field known as educational neuroscience is an increasing concern that educational practices and programs should be evidence-based, however; the idea that neuroscience could potentially influence education is controversial. One of the criticisms, regarding application of the data produced in this discipline, concerns the artificiality of neuroscientific experiments and the oversimplified nature of the tests used to investigate cognitive processes in educational contexts. The simulations may not account for all of the variables present in real classroom activities. In this study, we aim to get a step closer to the formation of data-supported classroom methodologies by employing functional near-infrared spectroscopy (fNIRS) in various experimental paradigms to pinpoint the mechanisms involved in education. First, we present two hyperscanning scenarios designed to explore mechanisms underlying cognitive processes in realistic interdisciplinary contexts, i.e. the classroom. In a third paradigm, we present a case study of a single student evaluated with fNIRS and mobile eye-tracking glasses. These three experiments are performed to provide proofs of concept for the application of fNIRS in scenarios that more closely resemble authentic classroom routines and daily activities. The goal of our study is to explore the potential of this technique in hopes that it offers a deeper understanding of the teaching-learning process during teacher-student interactions.